Prediction of intellectual capital based on knowledge leadership components from the perspective of school teachers - Chepeleva , Natalia; Smulson, Maryna; Rudnytska, Svitlana; Shylovska, Olena; Hutsol, Kyrylo (Interacción y Perspectiva, 2024)
The present research was conducted with the aim of investigating the relationship between knowledge leadership and intellectual capital in the schools. In terms of purpose, this research is of applied type, and descriptive correlation in terms of data collection method. The statistical population of this research is all the primary school teachers of X, (n= 325 people), from which a sample of 176 people was selected using a simple random sampling method based on Morgan’s sample size table, and the required data was collected. Viitala questionnaire (Viitala, 2004) was used to measure the knowledge leadership variable, and the Bontis model was used for intellectual capital. The formal and content validity of the tools was calculated using experts’ opinions, and the obtained reliability using Cronbach’s alpha method for knowledge leadership and intellectual capital was 0.95 and 0.88, respectively. Pearson’s correlation coefficient test, one-sample T, and regression analysis were used to analyze the data. The results of the research indicate that the current state of knowledge leadership and intellectual capital is above average, and the components of knowledge leadership (tendency to learn, supportive atmosphere of learning and support for the individual and group learning process) have a positive and significant relationship with intellectual capital; and among the components of knowledge leadership, only the component of tendency to learn is a significant predictor of intellectual capital. The results of this research can be used to develop the human capital of organizations.